PENGARUH KOMPENSASI KERJA DISIPLIN KERJA DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH MENENGAH KEJURUAN (SMK) DI YAYASAN PENDIDIKAN PEMBANGUNAN PERSADA KABUPATEN KEBUMEN (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
This research aims to determine (1). The influence of compensation on teacher performance to, (2) the influence of the teachers discipline on teacher performance, (3) Whether or not the influence of principal leadership teacher performance. (4) The influence of compensation, discipline, principal leadership. And environment teacher working simultancously on the performance.This research was conducted in Yayasan Pendidikan Pembangunan Persada district Kebumen. The population of this study the teacher Vocational Senior High School (SMK) Pembangunan 1 Kutowinangun and SMK Pembangunan 2 Kutowinangun Kebumen regency. Data collection techniques using the method of documentation and questionnaire. The techniques of data analysis using regression analysis and partial correlation, with terms of data analysis before being tested using the normality test and linearity test with a significance level of 5%.The results of research concluded that: (1). There is a positive and significant influence of compensation, teachers discipline and principal leadership on teacher performance and significant level, it mean that the hypothesis verified. (2) There is positive and significant influence compensation on teacher performance. (3). There is positive and significant influence the discipline of teachers to teacher on performance. (4). There is significant influence between the principal leadership on teacher performance.Â